Sensory and Physicochemical Characteristics of Semi-dry fermented Beef Sausages produced with Fresh Ripe Plantain - Worlah Yawo Akwetey; Awuni, Bernard Yaw; Yeboah Elizabeth (Turkish Journal of Agriculture: Food Science and Technology, 2023)
Fermented sausages are stable meat items typically prepared from comminuted mixtures of meat, spices, and salts and permitted to ripe under controlled conditions, where bacteria produce lactic acid quickly and reliably from added sugars in the form of dextrose. This study assessed the possibility of using fresh ripe plantain (FRP) in semi-dry fermented beef sausages. FRP was used at 0% (T0), 5% (T1) and 10% (T2). A fourth treatment with 0.5% dextrose without any FRP (T3) was produced. The products were evaluated for proximate compositions, pH, cooking loss as well as sensory attributes. No significant differences existed between T0, T1, T2 and T3 in terms of appearance, flavor, aftertaste and texture, however significant differences were recorded in tenderness, juiciness and acceptability. Cooking loss and water holding capacity ranged between 31.83 (T0) to 36.53 (T3) and 4.40 (T3) to 14.74 (T2) respectively. The pH recorded after 36 hours of fermentation ranged from 4.20 (T3) to 5.36 (T0). Using FRP resulted in appreciable decreases in costs of producing semi-dry fermented beef sausages from 20.50 to 16.46 Ghana Cedis per kg. It was concluded that fermented beef sausages could be made with 5% fresh ripe plantain without any adverse effects on consumer acceptability.